SCHOOL PSYCHOLOGY AND INCLUSION OF AUTISM STUDENTS: CHALLENGES IN THE BRAZILIAN CONTEXT - Coelho, Gilson Gomes [UNESP]; Cruz, Adriana Nunes da (Univ Federal Mato Grosso Sul, 2023)
This study aims to investigate the inclusive processes and practices of autistic students in regular schools. This investigation consists of an integrative literature review, which is broader and capable of covering various forms of studies and effective results that propose a better understanding of the studied phenomenon to the researcher. 20 studies were selected between the years 2003 and 2021 to compose the review, the text survey was carried out through the Google Scholar database, then by reading the title and abstract. The results showed that inclusive policies broke the paradigms of a traditional and formalist school for a revolutionary school through the concept of school inclusion, however the investigated data also showed that despite the changes that occurred both in the school and in the school environment there are still a series of challenges. factors that make it difficult for autistic students to enter and remain in regular schools. As for the work of the school psychologist, it was possible to verify that this professional is still looking for a crystallization of his field of action within schools and faces stigmas aimed at the medicalization of his practices.
Keywords: School inclusion; School psychology; Regular school; Autism